2020
DOI: 10.20900/agmr20200016
|View full text |Cite
|
Sign up to set email alerts
|

Why Loneliness Interventions Are Unsuccessful: A Call for Precision Health

Abstract: Background: Loneliness has drawn increasing attention over the past few decades due to rising recognition of its close connection with serious health issues, like dementia. Yet, researchers are failing to find solutions to alleviate the globally experienced burden of loneliness. Purpose: This review aims to shed light on possible reasons for why interventions have been ineffective. We suggest new directions for research on loneliness as it relates to precision health, emerging technologies, digital phenotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…These interventions have typically involved improving an individual's social skills, their ability to harness social support, increasing their opportunities for social contact, or addressing their maladaptive thoughts. However, results from systematic reviews have generally indicated that such interventions have weak and inconsistent effects (Akhter-Khan & Au, 2020;Cacioppo et al, 2015), with those focusing on social cognitions tending to be most beneficial (Masi et al, 2010). This failure to find strong effects is also observed in a recent review of COVID-19 e-mental health solutions to assist care workers, which reported a lack of empirical evidence of success as well as plentiful evidence of challenges and lack of uptake (Drissi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These interventions have typically involved improving an individual's social skills, their ability to harness social support, increasing their opportunities for social contact, or addressing their maladaptive thoughts. However, results from systematic reviews have generally indicated that such interventions have weak and inconsistent effects (Akhter-Khan & Au, 2020;Cacioppo et al, 2015), with those focusing on social cognitions tending to be most beneficial (Masi et al, 2010). This failure to find strong effects is also observed in a recent review of COVID-19 e-mental health solutions to assist care workers, which reported a lack of empirical evidence of success as well as plentiful evidence of challenges and lack of uptake (Drissi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Participants’ perspectives can help researchers gain insight into what works, what does not work, and why. This kind of understanding supports implementation of interventions at the right time to the right person, enhancing their effects, and addressing the urgent need for precise, theory-informed interventions to address an individual’s needs (Akhter-khan & Au, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Loneliness has two components: an emotional component (unpleasant, negative feeling) and a social cognition component (perception of social disconnection from other people with a desire to be connected) (Badcock et al, 2022). Loneliness can also be a transient normal experience or chronic with negative physical and mental health consequences (Akhter-Khan et al, 2020;Qualter et al, 2015).…”
Section: The Problem Condition or Issuementioning
confidence: 99%
“…Therefore, there is no one-size-fits-all approach, and it is important to tailor appropriate interventions to individuals' needs and contexts (Akhter-Khan et al, 2020;Fakoya et al, 2020;Mann et al, 2017).…”
Section: The Problem Condition or Issuementioning
confidence: 99%